Reviving Traditional Games: An Effective Medium for Enhancing Primary School Students’ Creativity — A Literature Review - Amelia, Rizky; Tatiah, Tatiah (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
In the current digital era, traditional games are increasingly being marginalized and regarded as obsolete. Nevertheless, a closer examination reveals that traditional games possess distinctive features that not only make them engaging but also offer valuable educational benefits. This study aims to explore the potential of traditional games in fostering creativity among primary school students. The primary objective is to investigate how these culturally rooted games can contribute to the development of students’ creative abilities. This research adopts a systematic literature review approach, involving the identification, selection, and analysis of relevant scholarly sources. A total of six peer-reviewed articles were examined based on the following keywords: creativity, traditional games, and student development. The findings suggest that traditional games can effectively enhance students' creativity through the use of strategic thinking, problem-solving, and the manipulation of game tools to achieve success. Furthermore, when traditional games are adapted or modified by educators, they become more engaging and serve as innovative tools for creative learning in the primary education context.